2015
DOI: 10.5935/0103-507x.20150027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in respiratory mechanics during respiratory physiotherapy in mechanically ventilated patients

Abstract: ObjectiveTo evaluate the changes in ventilatory mechanics and hemodynamics that occur in patients dependent on mechanical ventilation who are subjected to a standard respiratory therapy protocol.MethodsThis experimental and prospective study was performed in two intensive care units, in which patients dependent on mechanical ventilation for more than 48 hours were consecutively enrolled and subjected to an established respiratory physiotherapy protocol. Ventilatory variables (dynamic lung compliance, respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
2
14
0
3
Order By: Relevance
“…The technique of manual hyperinflation and thoracic compression were chosen for the control group because these techniques are used to remove secretions in intubated patients with some reports of success in the literature. [2][3][4] We agree with Guimarães and Rocha that the heterogeneity of individuals may generate bias in studies measuring the quantity of secretions; however, as shown in Table 1 of our report, 1 both groups show homogeneity for previous pathologies, comorbidities, and other factors, reducing the possibility of selection bias. The randomized clinical trial design was chosen to reduce the possibility of bias, especially with the sample size of 180 subjects, which was based on findings with the same design in a smaller sample size.…”
Section: Mechanical Insufflation-exsufflation Is Safe In Mechanicallysupporting
confidence: 77%
See 1 more Smart Citation
“…The technique of manual hyperinflation and thoracic compression were chosen for the control group because these techniques are used to remove secretions in intubated patients with some reports of success in the literature. [2][3][4] We agree with Guimarães and Rocha that the heterogeneity of individuals may generate bias in studies measuring the quantity of secretions; however, as shown in Table 1 of our report, 1 both groups show homogeneity for previous pathologies, comorbidities, and other factors, reducing the possibility of selection bias. The randomized clinical trial design was chosen to reduce the possibility of bias, especially with the sample size of 180 subjects, which was based on findings with the same design in a smaller sample size.…”
Section: Mechanical Insufflation-exsufflation Is Safe In Mechanicallysupporting
confidence: 77%
“…They suggest that secretion removal occurred predominantly from central airways, and we agree with this statement; however, we emphasize that this is the main objective of the maneuvers for respiratory secretion removal. 2,3 It is impossible to know how long the effect of the maneuver may last (30 min or 4 h), but it is reasonable to suggest that it follows the performance already demonstrated in patients with chronic neuromuscular disease. Because the hyperinflation technique was applied as part of routine patient care, there were no pressure or volume measurements during hyperinflation, and therefore it is not possible to affirm that this would displace more peripheral secretions than the 40 cm H 2 O pressure exerted by mechanical insufflationexsufflation.…”
Section: Mechanical Insufflation-exsufflation Is Safe In Mechanicallymentioning
confidence: 99%
“…Compreender os mecanismos fisiológicos da dor é importante para entender o mecanismo de ação dos analgésicos: os opioides inibem os impulsos aferentes no sistema nervoso central; os anestésicos locais interrompem diretamente a condução do impulso doloroso; e os anti-inflamatórios não esteroides impedem a sensibilização dos nociceptores que ocorre nos processos inflamatórios [24]. Estudos demonstram que a fisioterapia respiratória provoca alterações hemodinâmicas momentâneas no paciente crítico [25,26]. No estudo de Moreira et al [26] a intervenção fisioterapêutica promoveu alterações ventilatórias, como aumento da complacência pulmonar dinâmica e do volume corrente e redução da resistência do sistema respiratório; além dessas, aquele estudo também apontou para alterações hemodinâmicas como incremento da SpO 2 e elevação imediata, porém não sustentada, da FC, em consequência da estimulação traqueal que provoca o aumento da atividade simpática, resultando em taquicardia.…”
Section: Discussionunclassified
“…Estudos demonstram que a fisioterapia respiratória provoca alterações hemodinâmicas momentâneas no paciente crítico [25,26]. No estudo de Moreira et al [26] a intervenção fisioterapêutica promoveu alterações ventilatórias, como aumento da complacência pulmonar dinâmica e do volume corrente e redução da resistência do sistema respiratório; além dessas, aquele estudo também apontou para alterações hemodinâmicas como incremento da SpO 2 e elevação imediata, porém não sustentada, da FC, em consequência da estimulação traqueal que provoca o aumento da atividade simpática, resultando em taquicardia. Contudo, tal alteração hemodinâmica não foi observada neste estudo, o que pode ser explicado pelo nível de sedação e analgesia em que se encontravam os pacientes e/ou pelo reduzido tamanho amostral.…”
Section: Discussionunclassified
“…Therefore, patient survival rates do not depend only on factors present at the beginning of ventilation support, but also on development and handling of these factors throughout hospitalization. For this reason, proper conduct associated with a thorough clinical assessment by medical teams is required and must always be up to date (Martins, Botti, Castro, Aguiar & Sleutjes, 2005;Teixeira, Gomes & Coelho, 2013;Moreira, Teixeira, Savi & Xavier, 2015).…”
Section: Introductionmentioning
confidence: 99%